Population Pharmacokinetics Modeling of Levofloxacin In Rabbit By Intravenous Bolus Injection and Peroral Administration - Akhmad Kharis Nugroho; Puspa Dwi Pratiwi; Shesanti Citrariana; Endang Lukitaningsih; Lukman Hakim (Universitas Gadjah Mada, 2021)
The population-based approach has been widely applied to describe the pharmacokinetic profile of many drugs. The aim of this current research was to study the implementation of the population-based pharmacokinetics of levofloxacin in rabbits administered by intravenous bolus injection and peroral delivery. Modeling analyses were performed using Monolix, one of the alternative tools for the population-based approach. Monolix works based on the Stochastic Approximation Expectation-Maximization (SAEM) method. The analysis was performed based on the population model using one-compartmental and two-compartmental disposition models. The combination error model was used during the analyses. Modeling appropriateness was determined based on the goodness of fit analyses, i.e., 1) the individual fit, 2) the observed versus population prediction values; and 3) the observed versus individual prediction values Plasma concentration profiles of levofloxacin by intravenous bolus injection and oral administration are better described by an appropriate model using a two-compartmental disposition model. All goodness of fit analyses demonstrates the power of the chosen model. However, the estimated disposition parameter values obtained based on the intravenous bolus injection and peroral administration are different for each subject. To confirm this phenomenon, we performed a simultaneous fitting of all intravenous bolus as well as peroral administration data. The goodness of fit analyses indicates an adequate fitting of all data.